Émile Durkheim i tęsknota za wspólnotowością - Kostyło, Piotr (Rocznik Pedagogiczny, 2019)
This article analyzes the problems of community life as explored in Emile Durkheim’s texts, partic- ularly his lectures published under the title Moral Education. The starting point is the tension, char- acteristic of modern society, between the need to express one’s self within the community and the need to assert individual autonomy. The thesis presented here is that Durkheim looks for the sources of contemporary community life through the impact of school and professional groups, instead of the traditional influence of the family and Church. The article examines Durkheim’s argumentation relevant to justifying the thesis. In the final point, two lines of criticism of the Durkheimian concept, the spiritual and the Marxist, are deemed moot, as is the line of comparison between Durkheim’s approach and Zbigniew Kwieciński’s concept of community life.